The History and the Foreseeable Future of Road Tolling in Hungary - Török, Ádám; Siposs, Árpád; Mészáros, Ferenc (Promet - Traffic&Transportation, 2012)
The main scope of this paper is to present the historical background and the foreseeable future of the Hungarian road tolling. In the introduction the authors have investigated the historical dataset of motorway constructions and analysed the unequal extension of motorway system in time and space. In this article the authors are considering road tolling as an instrument of financing road infrastructure investment and the maintenance and controlling possibilities of traffic flows. KEYWORDS: road transportation, reduction of travel time, positive external effect